Crystal structure of 1,1′-(butane-1,4-diyl)bis(3-propyl-1H-imidazol-3-ium) bis(hexafluoridophosphate), C32H56F24N8P4 - Zhou Yao-Hong; Nie Xu-Liang; Xiong Wan-Ming; Peng Da-Yong; Zhang Xiao-Hua (Zeitschrift für Kristallographie - New Crystal Structures)
C32H56F24N8P4, triclinic, P1‾$P‾{1}$ (no. 2), a = 8.6769(13) Å, b = 9.8858(14) Å, c = 14.510(2) Å, α = 102.564(2)°, β = 94.461(3)°, γ = 92.152(3)°, V = 81.710(2) Å3, Z = 1, Rgt(F) = 0.0692, wRref(F2) = 0.2245, T = 296(2) K.